Hope Springs Eternal: The Image of South Africa in Swedish Media - Ylva Rodny-Gumede (The Thinker, 2023)
When South Africa is covered in the Swedish media, the focus is often on the history of South Africa, the role of Sweden in the anti-apartheid movement and, in more recent years, the political and socio-economic landscape of post-apartheid South Africa, marked by increased wealth gaps, social unrest, and corruption. How South Africa is covered by foreign media is important and politicians, as well as businesses and organisations such as Investment South Africa, Brand South Africa, and South African Tourism, keep a keen eye on the media as a gauge for maintaining diplomatic relations, as well as for attracting foreign investment. As a former journalist who has covered South Africa for Scandinavian media, I have had ample opportunity to ponder and research the media coverage of South Africa and the African continent in the Swedish media, as well as Scandinavian and wider international media. Drawing upon my own experience, as well as an analysis of coverage of South Africa in the Swedish news media, I ask what the image of South Africa is in the Swedish media, how this has changed over the last 30 years and, importantly, what this might mean for South African-Swedish relations?